FREQUENCY OF SEROREACTORS TO LAWSONIA INTRACELLULARIS IN COMMERCIAL PIG FARMS - Calderón A., Astrid (2009)
The objective of this study was to detect the presence of Lawsonia intracellularis antibodies in commercial swine herds in the Peruvian departments of Ica, Arequipa, La Libertad and Lambayeque. The antibodies were detected using the Indirect Immunofluorescence Antibody Technique (IFAT) in serum samples of 293 animals in five different age groups. La Libertad department was the most affected (14.6%) and female breeders were the most affected age group (23.1%). Positive results were found in 5.5 ± 0.6% of the samples. The results showed that L. intracellularis is an enteric ethiologic agent that affects the commercial swine production system of Peru.